A study on the biocompatibility of two possible retrograde filling materials - Lipumano, Lulette F.
A number of materials have been used as retrograde filling materials. The objective of this study was to find out which retrograde filling material is most biocompatible through comparing bone and soft tissue reactions to IRM, Dyract and Ketac-Silver. Under local anesthesia, the lower left incisor was extractedfrom each animal. The test materials were placed inside a 3mm long X 1mm diameter polyethylene tube and each tube was implanted in the extraction site. The animals were sacrificed at 14, 42 and 90 days, and the mandibles were dissected and prepared histologically. The inflammatory reaction was assessed by quantifying the number of plasma cells/lymphocytes, PMN's and osteoclasts present within the area of the implant. Osseous response was assessed by determining the presence or absence of bone formation by quantifying the presence or absence of osteoblasts. No statistical difference was found among the three materials tested with regards to soft tissue inflammatory reaction in the different time intervals. On the other hand, with regards to osseous response, a statistical difference was found in the 14 day specimen group since only Ketac-Silver manifested bone formation at this time interval. This study indicates that all tested materials are biocompatible, and may serve as support for the use of Dvract and Ketac-Silver as possible retrograde filling materials.